2008
DOI: 10.1007/s11258-008-9519-6
|View full text |Cite
|
Sign up to set email alerts
|

Host trait preferences and distribution of vascular epiphytes in a warm-temperate forest

Abstract: To illustrate the ecological factors and process leading to the observed diversity patterns of vascular epiphytes, we examined the effect and importance of host tree traits on epiphyte richness and spatial aggregation of epiphytes. The study was conducted in warm-temperate forest in Japan. The recorded host traits were diameter, height, species, habitat topography, and growth rate, and we analyzed the effects and importance of these traits on three species groups: total epiphytic species, epiphytic orchid spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 30 publications
4
32
1
6
Order By: Relevance
“…This is in line with the results of Migenis and Ackerman (1993), while Callaway (1998) among epiphytic vascular species found some examples of such strong preference. Our study supports the earlier findings that large sized trees offer more space for the growth of orchid, and more substrate (humus) for the germination of their seeds and subsequent growth of seedlings (Heitz 1999;Bergstrom and Carter 2008;Hirata et al 2009). …”
Section: Microhabitat Of Rhynchostylissupporting
confidence: 92%
“…This is in line with the results of Migenis and Ackerman (1993), while Callaway (1998) among epiphytic vascular species found some examples of such strong preference. Our study supports the earlier findings that large sized trees offer more space for the growth of orchid, and more substrate (humus) for the germination of their seeds and subsequent growth of seedlings (Heitz 1999;Bergstrom and Carter 2008;Hirata et al 2009). …”
Section: Microhabitat Of Rhynchostylissupporting
confidence: 92%
“…Host trees provide the substrate for epiphytes, so establishment seems to be affected by host tree traits (Hirata et al 2008). The result showed that there were 32 species host trees for epiphytic orchid in this area.…”
Section: Host Treementioning
confidence: 89%
“…are suitable host trees for a number of orchid species. Host tree species determines traits, such as bark characteristics (Hirata et al 2008). According to Yulistyarini (2001), Host trees such as Cratoxylum sp., Vitex sp.…”
Section: Host Treementioning
confidence: 99%
“…A importância e a contribuição dos forófitos para a riqueza e a distribuição espacial de epífitas têm sido relatadas em estudos que buscam elucidar fatores ecológicos e processos que conduzem a padrões de diversidade observados no componente epifítico (Hirata et al 2009). Diversos autores demonstram que epífitas diferem em abundância entre forófitos (Benzing 1981;Bennett 1986;Ter Steege & Cornelissen 1989;Migenis & Ackerman 1993;Dejean et al 1995;Kernan & Fowler, 1995;Fontoura et.…”
Section: Introductionunclassified
“…Contudo, os resultados obtidos na maioria dos estudos demonstram que a presença e abundância de epífitas estão associadas a características das espécies hospedeiras (Frei & Dodson 1972;Schlesinger & Marks 1977;Medeiros & Jardim 2011), como arquitetura, textura e estabilidade da casca (Gentry & Dodson 1987;Hietz & Hietz-Seifert 1995;Fontoura et al 1997;Nieder et al 2000;Kersten et al 2009), e também pelo tempo em que eles estão disponíveis à colonização no ambiente (Benzing 1995a;Bonnet et al 2007). Hirata et al (2009) sugerem que o tamanho, estabilidade, e qualidade do hospedeiro são igualmente importantes na determinação da colonização epífitas. Entretanto, quando se considera a família Bromeliaceae, pouco se analisou sobre possíveis especificidades e relações com os forófitos e suas características.…”
Section: Introductionunclassified